Development of therapeutic garments for atopic dermatitis: Integrating functional textiles and clothing design - Wu, Yian; Ramli, Saiful Hasley; How, Kang Nien; Ho, Wen Chung; Lai, Oi Ming; Xiao, Min (Taylor and Francis, 2025)
Atopic dermatitis (AD) is a recurring inflammatory skin disorder with significant social and economic impacts. This study aimed to develop therapeutic garments suitable for daily wear by AD patients. Using silver-ion fabric with anti-inflammatory properties and breathable, moisture-wicking materials, three distinct T-shirt styles were designed through patient feedback, balancing aesthetics and functionality. The research methods included focus groups, co-design workshops, and wear trials. An infrared thermal imager and temperature-humidity sensors measured temperature and humidity changes at the chest, back, and underarms every minute under identical conditions to evaluate the heat dissipation and moisture management. The results demonstrated that the back-ventilation style (T-shirt ①) exhibited the best overall heat and moisture dissipation. This design leverages passive cooling through moisture evaporation, promoting rapid temperature reduction and moisture dissipation during daily activities or exercise, thereby alleviating skin heat sensations and reducing itching for AD patients.